Evaluation of Tabata Training Results on Changes in Body Composition of Overweight and Obese Adolescents - Noor Haq, Rr. Hazima Zavier; Muhammad; Pramono, Bayu Agung; Tri Ulul Albab, Muhammad Syaikha; Nurma Wijayanti, Marsyela Dwi; Tama Suwarno, Rizky Adi; Savitri, Erlina (Journal of Sport and Exercise Science, 2024)
Purpose: Obesity in adolescents is currently experiencing a significant increase. Caused by an unbalanced lifestyle and lack of physical activity. Materials and Methods: This study uses the Tabata method of physical exercise which aims to determine the impact of physical activity on body composition and weight loss in adolescents. This study used 30 samples of active college students who engaged in physical activity with moderate intensity, which is around 75-85%, for 30 minutes every day. This study used data collection methods with a descriptive approach and statistical analysis, such as the Wilcoxon test. The Wilcoxon test was used to see differences before and after doing physical activity Tabata exercise. Result: The results showed a significant difference in body composition before and after doing a physical activity program with the Tabata method regularly carried out 4 times a week for 3 weeks, with a p value <0.05, then training using the Tabata method in this study can only reduce Body Weight (BW), Body Mass Index (BMI), and Body Fat Percentage (BFP). Conclusion: The conclusion of this study shows that physical exercise with the Tabata method can reduce body weight (BW), Body Fat Percentage (BFP), and Body Mass Index (BMI) in adolescents aged 18-21 years. this study shows that Tabata exercise has benefits in controlling weight and reducing the risk of non-communicable diseases such as diabetes, ischemic heart disease, and cancer. In addition, Tabata training can also improve the well-being of adolescents by increasing physical fitness and increasing self-confidence in adolescents, Tabata training can be an effective strategy and improve the overall quality of life of adolescents.